ANALISIS HUKUM TERHADAP PERAN ARTIFICIAL INTELLIGENCE (AI) DALAM DIAGNOSTIK MEDIS: KEWENANGAN DAN TANGGUNG JAWAB HUKUM - Rizki Pratami, Nadia; Fakhry Dzulfiqar, Muhammad (POLITEKNIK PIKSI GANESHA, 2024)
The development of artificial intelligence (AI) technology in the healthcare sector, particularly in medical diagnostics, has brought significant advancements in accuracy, speed, and efficiency of healthcare services. However, the use of AI also raises new legal challenges related to the authority to issue medical diagnoses and the determination of legal liability in cases of errors or patient harm. This study aims to analyze the legal framework governing the use of AI in medical practice in Indonesia and to examine the distribution of liability among medical personnel, healthcare institutions, and AI system developers. The research employs a normative juridical method with a statutory and case study approach. The findings indicate that, under current Indonesian law, AI is not recognized as a legal subject, and therefore, the authority to diagnose remains with licensed medical professionals. Nevertheless, the absence of specific regulations creates a legal vacuum concerning civil and criminal liability in cases of AI system failure. Consequently, regulatory reform is needed to clearly define the responsibilities and limits of each party involved in the digital health ecosystem, in order to protect patient rights and provide legal certainty for service providers.